The influence of sustainable responsible investment (SRI) on portfolio investment by institutional investors : a South African case study - Ogbuka, Blessing Anwuri (My University, 2015)
Over the years many studies have noted the negative effect of business activities on the environment. As a result there has been increasing pressure by environmental interest groups and other stakeholders on companies to carry out their activities in a socially responsible manner. This pressure has been directed mostly by institutional investors on the importance of supporting environmental sustainability through investing in socially responsible companies since they have more funds at their disposal. By being signatories to the UN PRI, institutional investors pledge to consider the three key sustainability issues, that is, environmental, social and governance (ESG) issues in their investment decisions. The Code for Responsible Investing in South Africa (CRISA) also encourages the consideration of ESG criteria by institutional investors when making investment decisions. However, these institutional investors also have a fiduciary responsibility to the owners of the funds and are expected to provide returns to them since these funds are held in trust for the latter. The purpose of this study, therefore, is to examine whether institutional investors in South Africa are influenced by ESG concerns in their investment decisions by investing in a socially responsible manner. An exploratory qualitative content analysis was conducted on the annual, integrated and sustainability reports of the investee companies to examine whether their business activities are carried out in a sustainable manner. The findings reveal that environmental concerns do not yet receive attention to a large extent when compared with social or governance issues which show that the materiality of such ESG issues is the main focus. Institutional investors’ investment power can be used to influence companies to carry out their business activities in a more sustainable manner for a cleaner and safer environment.
Thesis (M. Com. (Accounting)) -- University of Limpopo, 2015
Keywords: Socially responsible investment; Institutional investors; Environmental; Environmental, social and governance issues; Investments; Business; Investments -- Moral and ethical aspects